Legal Protection Against Personal Data In Online Loan Transactions - Fataya Widi; Abdul Qahar; Aan Aswari (Golden Ratio of Law and Social Policy Review (GRLSPR), 2021)
This study aims to determine the legal protection of personal data in online transactions and determine the legal consequences of individual data violations committed by online business entities. This study indicates that legal protection for personal data in online loan transactions is carried out through preventive measures, namely preventing disputes or legal problems. And through repressive measures, namely resolving disputes to the authorities carried out by both parties. The legal consequences carried out by online loan business entities are causing material losses and also material losses by demanding compensation. This research recommendation requires a regulation regarding the protection of personal data in a special regulation that contains a comprehensive and comprehensive and the need to establish a clear and definite legal protection institution. So as not to cause harm to either party.